EXPERIMENTAL STUDIES OF THE INTERACTION OF AQUEOUS METAL CATIONS WITH MINERAL SUBSTRATES: LEAD, CADMIUM, AND COPPER WITH PERTHITIC FELDSPAR, MUSCOVITE, AND BIOTITE - Farquhar M.L.; Vaughan D.J.; Hughes C.R.; Charnock J.M.; England K.E.R. (My University, 1997)
The interactions between each of the metal ions copper(II), cadmium(II), and lead(II) in aqueous solution and the surfaces of the minerals muscovite, biotite, and perthitic feldspar have been studied using batch sorption experiments and X-ray photoelectron (XPS) and X-ray absorption (XAS) spectroscopies. The purpose of the work has been to establish the extent of removal from solution of these metal ions by interaction with the mineral surfaces and the mechanisms involved (whether ion exchange, precipitation, or adsorption).The experiments utilised both powdered samples and flat polished or cleaved surfaces of natural minerals which were characterised compositionally and structurally by electron probe microanalysis and X-ray diffraction. Reaction solutions contained Cu(II), Cd(II), or Pb(II) in a background electrolyte of NaNO3 (0.1 or 0.01 M) at a pH of 5.4 +/- 0.2 with a wide range of initial concentrations. The extent of uptake of each of the metals by a particular mineral substrate was measured by analysis of the liquid portion separated by centrifugation after a controlled period of exposure (solution analyses were performed by atomic absorption spectroscopy or by inductively coupled plasma mass spectroscopy as appropriate). The data obtained were used to plot sorption isotherms for the various metal ions and substrates showing the dependence of uptake on initial concentration of metal in solution and background electrolyte concentration. Studies of the reacted mineral surfaces using XPS were used to identify the chemical speciation and bonding environment of Cu, Cd, and Pb present at the surface and to assess surface coverage in planar surface samples and whether significant infiltration of the metal cation into the mineral surface had occurred. Parallel studies using XAS (in particular Extended X-ray Absorption Fine Structure Spectroscopy-EXAFS) were employed to determine the local environments of Cu, Cd, and Pb at the surface of powdered mineral samples. Planar surfaces of muscovite, biotite, and perthitic feldspar exposed to Cu(II) and of muscovite exposed to Cd(II) were also studied using Reflection Extended X-ray Absorption Fine Structure (REFLEXAFS) spectroscopy.The results show that muscovite, biotite, and perthitic feldspar have surfaces that can strongly interact with (and remove) particularly Cu(II) and Pb(II) in such mildly acidic aqueous solutions. Biotite also strongly interacts with Cd(II) in solution. Generally biotite provides the most reactive mineral surface followed by muscovite, with perthitic feldspar being the least reactive. Of the possible mechanisms for removal of metals under the conditions of these experiments, precipitation was not observed, but three other mechanisms (inner-sphere complexation, outer-sphere complexation, and ion exchange) were all observed. The inner-sphere complexation and ion exchange mechanisms often take place in combination: however, Pb(II) forms no outer-sphere complexes on the surfaces of these minerals, and Cd(II) forms only outer-sphere complexes with perthitic feldspar and muscovite. Cu(II) in solution promotes the release of K+ from the surface region of muscovite and, particularly, biotite, and subsequent uptake of Cu(II) by ion exchange.These findings have important environmental implications and show the significant role that major rock-forming aluminosilicates may play in the geochemical cycling of Cu(II), Cd(II), and Pb(II).